Neuromodulatory Effects of Guanine-Based Purines in Health and Disease - Tasca, Carla I.; Lanznaster, Débora; Oliveira, Karen A.; Fernández-Dueñas, Victor; Ciruela, Francisco (Frontiers in Cellular Neuroscience, 2018)
The function of guanine-based purines (GBPs) is mostly attributed to the intracellular modulation of heteromeric and monomeric G proteins. However, extracellular effects of guanine derivatives have also been recognized. Thus, in the central nervous system (CNS), a guanine-based purinergic system that exerts neuromodulator effects, has been postulated. The thesis that GBPs are neuromodulators emerged from in vivo and in vitro studies, in which neurotrophic and neuroprotective effects of these kinds of molecules (i.e. guanosine) were demonstrated. GBPs induce several important biological effects in rodent models and have been shown to reduce seizures and pain, stabilize mood disorder behaviour, and protect against gliomas and aging-related diseases such as ischemia, and both Parkinson’s and Alzheimer’s disease. In vitro studies to evaluate the protective and trophic effects of guanosine, and of the nitrogenous base guanine, have been fundamental for understanding the mechanisms of action of GBPs, as well as the signalling pathways involved in their biological roles. Conversely, putative GBP receptors have not yet been identified, although selective binding sites for guanosine have been identified in rat brain membranes. In addition, GBP neuromodulation may depend on the capacity of GBPs to interact with well-known membrane proteins in glutamatergic and adenosinergic systems. Overall, in this review we present up-to-date GBP biology, focusing mainly on the mechanisms of action that may lead to the neuromodulator role of GBPs observed in neurological disorders.